Feasibility Analysis of Animation Video Learning Media Based Powtoon on Lagrange Mechanics - Afifah, Nabila; Putri, Nofita Dewi; Maheta Anisa Haqqu; Setiaji, Bayu (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2021)
Physics learning related to mathematical equations needs to be arranged in an interesting, fun, and easy way to understand the material. Learning that is packed with fun will attract students' interest in learning more. This study aims to test the feasibility of animation video learning media based Powtoon on Lagrange mechanics material. This research is research and development using the ADDIE model design (analysis, design, development, implementation, and evaluation). The feasibility test data were analyzed using descriptive statistical analysis. The results showed that the animated video learning media based Powtoon was feasible to use in physics learning for Lagrange mechanics. The findings of this study can be used as a further reference for researchers who will conduct Lagrange mechanics learning experiments using animated videos based on Powtoon.